Hubungan Karakteristik Perawat terhadap Pelaksanaan Sasaran Keselamatan Pasien Pasca Akreditasi Rumah Sakit “X” di Kota Palembang Tahun 2018 - Raden Surahmat; Meri Neherta; Nurariati Nurariati (Universitas Batanghari Jambi, 2019)
Safety of patients, nurses, companions and visitors is the main priority of nursing services in hospitals, because quality services will have an impact on hospital accreditation assessments. This study aims to determine the relationship between the characteristics of nurses on the implementation of patient safety goals after accreditation of